2011
DOI: 10.1007/s12010-011-9256-5
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Metabolite Pathways and Antibiotic Production Variations of a Novel Streptomyces sp. M3004 Depending on the Concentrations of Carbon Sources

Abstract: To determine the variations of growth, some key enzyme activities such as glucose kinase (GK), glucose-6-phosphate dehydrogenase (G6PDH), α-ketoglutarate dehydrogenase (KGDH), and isocitrate lyase (ICL) besides metabolite levels of pyruvate and antibiotic production of newly isolated Streptomyces sp. M3004 were grown in culture media which contain 10-20 g/l concentration with either glucose or glycerol as carbon source. Biomass and intracellular glucose and glycerol levels of Streptomyces sp. M3004 showed posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…PB 0 , the precursor of the antifungal drug caspofungin, is a secondary metabolite of the fungus G. lozoyensis (Bills et al, 1999;Youssar et al, 2012), and its biosynthesis is affected by the types and concentrations of nutrients in the medium. Among them, the carbon source is a key factor affecting cell growth and PB 0 production (Sanchez and Demain, 2002;Kayali et al, 2011). However, recent research on G. lozoyensis has mainly focused on biosynthetic gene clusters and fermentation regulation strategies (Chen et al, 2013(Chen et al, , 2015Song et al, 2018a,c), while the mechanisms that regulate the carbon source metabolism are still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PB 0 , the precursor of the antifungal drug caspofungin, is a secondary metabolite of the fungus G. lozoyensis (Bills et al, 1999;Youssar et al, 2012), and its biosynthesis is affected by the types and concentrations of nutrients in the medium. Among them, the carbon source is a key factor affecting cell growth and PB 0 production (Sanchez and Demain, 2002;Kayali et al, 2011). However, recent research on G. lozoyensis has mainly focused on biosynthetic gene clusters and fermentation regulation strategies (Chen et al, 2013(Chen et al, , 2015Song et al, 2018a,c), while the mechanisms that regulate the carbon source metabolism are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…During the culture process, nutrient components and metabolic compounds in the medium have a great influence on the synthesis of SMs (Sanchez and Demain, 2002). Among them, the carbon source is the most important influencing factor, and optimization of carbon sources has been the subject of continuous research (Kayali et al, 2011). Tkacz et al (1993) found that using 100 g/L mannitol as the sole carbon source improved the yield of PB 0 to 800 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…And the cell debris has been removed through centrifugation at 10,000 rpm per 10 min at 4°C. The supernatants were collected and the protein content of the mixture was examined by xylene brilliant cyanine G250 (Kayali et al 2011). In addition, Na ?…”
Section: Measurement Of Release Of 260 and 280 Nm Uvabsorbing Materialsmentioning
confidence: 99%
“…e activities of POD and CAT were explored by a POD assay kit and CAT assay kit, respectively. e content of the protein was determined by the Bradford method at 595 nm, and the standard curve was made using bovine serum albumin [22].…”
Section: Determination Of the Antioxidant Enzyme Assaymentioning
confidence: 99%